Analysis Of the Effectiveness of Using the Siks-Ng Application on Community Services in the Citof Prabumulih Using the Pieces Method - Niken Rahmanti; Nur Aini; Yuntari Purbasari (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2024)
Technological developments can influence several aspects, including government, politics and the economy. Effectiveness is something important, because effectiveness can be studied from various points of view and depends on who assesses and interprets it. Prabumulih City is one of the cities in South Sumatra province that has implemented the Siks-Ng information system. This research uses a descriptive method with a quantitative approach. The quantitative data in this research is the result of an online questionnaire distributed to user respondents or sub-district and sub-district operators in the city of Prabumulih. This analysis uses the PIECES method with six variables, namely Performance, Information, Control, Efficiency, Service. The results of the PIECES analysis of the use of the Siks-Ng application are performance analysis 4.42, information analysis 4.45, economics analysis 4.5, control analysis 4.41, efficiency analysis 4.55, service analysis 4.59. From all the analysis results, it can be categorized as very satisfied, meaning that the Siks-Ng application can provide convenience, effectiveness and satisfaction for users.